2016
DOI: 10.1021/acs.chemmater.5b04291
|View full text |Cite
|
Sign up to set email alerts
|

Monolayer Doping of Silicon through Grafting a Tailored Molecular Phosphorus Precursor onto Oxide-Passivated Silicon Surfaces

Abstract: K. Szeto from C2P2-LCOMS. ETH Zürich, CPE Lyon and UCBL are also acknowledged for their scientific support and the access to the process and characterization facilities. ASSOCIATED CONTENT Supporting Information. Experimental and computational details; in-situ IR and solid-state NMR spectra are available free of charge on the ACS Publications website.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
45
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 60 publications
0
45
0
Order By: Relevance
“…The absence of additional 8 correlations at 1.7 and 4.9 ppm support the attribution of the other isopropoxy ligand to be bound to a silicon rather than vanadium. This interpretation is further supported by the difference of chemical shift since alkoxide ligands bound to d 0 transition-metals are often greatly deshielded, 37,38 because of the presence of low lying empty d orbitals on the metal that modify the electronic structures of bonded ligands. 39 This observation is in line with elemental analysis results which indicated a C:V ratio of 5.5 as mentioned before, thus confirming that approximately 2 isopropoxide ligands remain on the silica surface.…”
mentioning
confidence: 94%
“…The absence of additional 8 correlations at 1.7 and 4.9 ppm support the attribution of the other isopropoxy ligand to be bound to a silicon rather than vanadium. This interpretation is further supported by the difference of chemical shift since alkoxide ligands bound to d 0 transition-metals are often greatly deshielded, 37,38 because of the presence of low lying empty d orbitals on the metal that modify the electronic structures of bonded ligands. 39 This observation is in line with elemental analysis results which indicated a C:V ratio of 5.5 as mentioned before, thus confirming that approximately 2 isopropoxide ligands remain on the silica surface.…”
mentioning
confidence: 94%
“…In that respect, we have demonstrated that the surface chemistry of a silica layer on passivated silicon wafers is analogous to that of high surface area silica nanoparticles and that identical surface species were found upon immobilization of molecules on both supports. 17,18 …”
mentioning
confidence: 99%
“…There are very few theoretical studies on the POSS structures. B3LYP, which is an accurate and well known method, is widely used for the POSS studies . Skelton compared MP2, B3LYP, and wB97XD methods for the interaction of POSS with CO 2 , N 2 , O 2 , CO, CH 4 , He, and H 2 O by keeping the cage structure fixed.…”
Section: Poss Models and Calculation Methodsmentioning
confidence: 99%